The effect of addition of oyster mushroom (Pleurotus sajor-caju) on nutrient composition and sensory acceptation of selected wheat- and rice-based products - Aishah, M. S.; Wan Rosli, W. I. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
Mushroom cultivation has been more popular recently in Malaysia. They are favoured due to their delicious flavour and low calorific value. Apart from that, they also contain high amount of protein and other essential nutrients. As recommended by food pyramid, people should take in more of their calories from whole grains-based foods than any other sources. Three selected carbohydrate based products namely rice-porridge (RP), paratha flat bread (PB) and conventional cake (CC) were formulated with dried Pleurotus sajor-caju (PSC) powder. All three products were analyzed for proximate analysis and sensory evaluation. Result shows the percentage of moisture, ash, fat and protein of RP increased in line with the levels of PSC powder used except for carbohydrate. Whereas for PB and CCs added with 2%, 4% and 6% PSC, the percentage of all nutrients were higher than control (0%) except for fat. Mushroom-based RP had significantly higher value of odour attribute as compared to control, with RP added with 6% PSC powder received the highest score. Meanwhile, mushroom-based PB received better score on textural attribute compared the control. In CC, panels prefer the cake added with 4% PSC powder as they gave higher scores for softness and flavour attributes. In conclusion, addition of PSC powder to partially replace rice and wheat flour in RP, CC and PB enhance essential nutritional components and well accepted by consumers. Thus, PSC powder can be considered to be utilized in carbohydrate–based food products with the purpose of enhancing nutrient compositions without affecting its sensory acceptance.